Ibn Thufail and His Contributions in the Field of Islamic Philosophy: Thoughts and Developments - Latif, Mukhlis (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2023)
Islamic philosophical thought is actually a study that discusses the essence and substance of the thinker. As an Islamic thinker, of course, various Islamic philosophical thoughts are related to Islamic teachings. This can be understood because Islam seems to be a